Ethnic artistic tradition as the object of Ukrainian ethnology - Fedorchuk, Olena (EtnoAntropologia, 2020)
The artistic component is a significant part of the ethnic tradition. However, the ethnic artistic tradition has not become active field of discussion in Ukrainian ethnology yet. The author offers her own concept of ethnic artistic tradition, based on empirical studies of the relatively young (just over 200 years) tradition of beaded decoration of the Ukrainian folk costume. The proposed concept takes into consideration the scientific achievements of the Ukrainian art criticism and ethnological sciences. The author of review article tries to activate discourse about ethnic artistic tradition. Such discourse can become interesting and productive area of modern ethnological studies, particularly in the context of «authorized heritage discourse» (AHD).